Can't forget: disruption of the right prefrontal cortex impairs voluntary forgetting in a recognition test. Issue 1 (2nd January 2020) - Xie, Hui; Chen, Yu; Lin, Yiqin; Hu, Xiaoqing; Zhang, Dandan
ABSTRACT: The causal influence of the dorsolateral prefrontal cortex (DLPFC) in voluntary forgetting remains unclear. Here, we employed repetitive transcranial magnetic stimulation (rTMS) over the right DLPFC to temporarily disrupt function of this brain region and examined its influence on an item-method directed forgetting (DF) task with both neutral and negative emotional memories. Participants were assigned to either an active or a sham rTMS group, in which we administered stimulation for 20 min before the DF task. We then examined the explicit and implicit DF effects with an explicit recognition and an implicit word completion test. We found that while participants in the sham group showed the classic DF effects in both explicit and implicit memory tests, temporally disrupting activity of the right DLPFC selectively reduced the DF effect on explicit recognition, but not on implicit word completion test. Our findings provide novel evidence that the right DLPFC plays a causal role in voluntary forgetting and support the direct inhibition account of voluntary memory control. Intriguingly, preserved implicit DF effects in the active stimulation group suggest that unintentional expressions of unwanted memories may be more sensitive to DF and less dependent on the right DLPFC.